Comparative Analysis of Low Lander Transcriptomes at Himalayas and Andes Reveals Differential Regulation of Erythropoiesis at Extreme Altitude - Sharma, Vandana; Sethy, Niroj Kumar (Defence Life Science Journal, 2024)
Systematic human expeditions to very high (≥ 3500 meters) and extreme altitudes (≥ 5500 meters) have documented marked changes in human physiology. However, only a handful of studies have reported lowlander transcriptome alterations at extreme altitudes. In this study, we compared the lowlander transcriptomes available in the literature for Chinese mountaineers (n=4, 3 males and 1 female)inthe Himalayas (Mount Xixabangma base camp, 5600 meters) and French mountaineers (n=8, all males) at Andes (La Rinconada, Peru, 5100 meters). We sought to find out significantly alteredpathways, gene networks, andtranscription factors (TFs) for each data set. We observed profound upregulation of GATA1 in the Himalaya transcriptome data set (+ 1.38-fold) in comparison tothe Andes data set (-1.36-fold). Core transcriptome analysis revealed that GATA1 upregulated erythropoiesis genes like KLF1, HBD, HBG, EPB42, ALAS2, and AHSP in the Himalayan dataset in contrast to the Andean data set.We also observed contrasting expression profiles ofKLF1 in the Himalayas (+1.22-fold) and Andes (-1.15-fold)for lowlander populations and differential expression regulation of its downstream target genes like AHSP, ALAS2, SLC4A1, EPB42,HBG2, andHBB.We also observed upregulation of SP1 (+ 2.46-fold) in the Himalayan transcriptome as compared to the Andean transcriptome which also regulates erythropoiesis genes along with GATA1. Our results indicate profound upregulation of erythropoiesis-promotingTFs and genes in Chinese mountaineers at extreme altitudes in contrast to French mountaineers at similar altitudes. Though our present analysis does not provide possible reasons for the observed differences inhypoxia-responsive erythropoiesis gene signatures, it certainly highlights ethnicity-dependenttranscriptome level variations in lowlanders at extreme altitudes.